EVALUATION ON ERADICATION OF MALNUTRITION AMONG UNDER-FIVE CHIDLREN IN COMMUNITY HEALTH CENTERS (CHC) OF BELU DISTRIC, NTT PROVINCE (CHC CASE STUDY WITH HIGHEST CASE OF MALNUTRITION) - AGUSTINA ABUK SERAN (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Background: Nutrient deficiency is a nutritional problem that affects thousands of under-five children in Indonesia. Many factors cause nutrient deficiency; two of which are not exclusively breastfeed infections disease nutritional problems, was 84,3%out of 67,539 under-five children Province. In Belu District in NTT, under-five children who suffered from nutrient deficiency were 33% and from malnutrition were 6,4%. In fact, under-five children who have died due to malnutrition are four children.Objective: To evaluate the eradication of malnutrition among under-five children in posyandu (Integrated services) of CHCs with highest case of malnutrition.Method: This was a case-study, evaluation research with a cross-sectional research design and a quantitative approach, supported with a qualitative approach. The independent variables were exclusive breastfeeding and the symptom of infectious disease and the dependent variables was nutritional status. Subjects were 200 children in posyandu of CHCs with the highest case of malnutrition taken with non probability sampling. Data were analyzed using univariable, bivariable and multivariable analyses.Results: Of 200 under-five children in this research, good nutritional status was 32,5%, bad nutritional status was 41,5% and poor nutritional status was 26%. The coverage of malnutrition early detection was still under 80%. Based on the findings, children who received exclusive breastfeeding were 21,5% and children who experienced the symptom of a disease were 45,5%. The prevalence of under-five children who did not receive exclusive breastfeeding and infectious disease was likely to present a greater risk of nutrient deficiency (RP=4.6; CI 95%=2.12-10.21 and RP-2.2; CI 9%=1.13-4.30). Maternal education affected the incidence of nutrient deficiency (RP=1.2; CI 95%=0.05– 2.95). Variable of maternal knowledge was significant statistically and practically.Conclusion: Exclusive breastfeeding, infectious disease, maternal education and knowledge were influential toward the incident of nutrient deficiency or malnutrition.